2013
DOI: 10.1080/10255842.2011.623673
|View full text |Cite
|
Sign up to set email alerts
|

A method for the field assessment of rolling resistance properties of manual wheelchairs

Abstract: This article presents an examination and validation of a method to measure the field deceleration of a manual wheelchair (MWC) and to calculate the rolling resistances properties of the front and rear wheels. This method was based on the measurements of the MWC deceleration for various load settings from a 3D accelerometer. A mechanical model of MWC deceleration was developed which allowed computing the rolling resistance factors of front and rear wheels on a tested surface. Four deceleration sets were conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 20 publications
1
20
0
2
Order By: Relevance
“…In addition, the effect of weight distribution on resistive loss varied according to the trajectory of motion. This result is consistent with those of Bascou et al, who studied rolling resistance of different wheelchair configurations and reported a 52 percent increase in the decelerations when the loads on the casters varied from 29 to 64 percent using the same wheelchair mass [14]. Similar observations were made by Sauret et al, who speculated that decelerations would continually increase as the distribution of total mass on the front wheels increased [16].…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, the effect of weight distribution on resistive loss varied according to the trajectory of motion. This result is consistent with those of Bascou et al, who studied rolling resistance of different wheelchair configurations and reported a 52 percent increase in the decelerations when the loads on the casters varied from 29 to 64 percent using the same wheelchair mass [14]. Similar observations were made by Sauret et al, who speculated that decelerations would continually increase as the distribution of total mass on the front wheels increased [16].…”
Section: Discussionsupporting
confidence: 91%
“…In Coutts' study, the decelerations during the first six trials were determined with an average CV of 7.1 percent on a hardwood floor [31]. Comparing the decelerations across studies is difficult since different coast-down studies used different wheelchair frames [14][15][16], wheels [13,16], and ground types [19,21,32]. However, with similar weight distribution (30% loading on casters), our deceleration values had a similar range as Sauret et al (from 0.05 to 0.25 m/s 2 ) on a hard, smooth surface [16].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations